What are the barriers to implementation of cardiopulmonary resuscitation training in secondary schools? A qualitative study - Christian Torp-Pedersen; Fredrik Folke; Tine Tjørnhøj-Thomsen; Carolina Malta Hansen; Line Zinckernagel; Morten Hulvej Rod (BMJ Open, 2016)
Objective Cardiopulmonary resuscitation (CPR) training in schools is recommended to increase bystander CPR and thereby survival of out-of-hospital cardiac arrest, but despite mandating legislation, low rates of implementation have been observed in several countries, including Denmark. The purpose of the study was to explore barriers to implementation of CPR training in Danish secondary schools.Design A qualitative study based on individual interviews and focus groups with school leadership and teachers. Thematic analysis was used to identify regular patterns of meaning both within and across the interviews.Setting 8 secondary schools in Denmark. Schools were selected using strategic sampling to reach maximum variation, including schools with/without recent experience in CPR training of students, public/private schools and schools near to and far from hospitals.Participants The study population comprised 25 participants, 9 school leadership members and 16 teachers.Results School leadership and teachers considered it important for implementation and sustainability of CPR training that teachers conduct CPR training of students. However, they preferred external instructors to train students, unless teachers acquired the CPR skills which they considered were needed. They considered CPR training to differ substantially from other teaching subjects because it is a matter of life and death, and they therefore believed extraordinary skills were required for conducting the training. This was mainly rooted in their insecurity about their own CPR skills. CPR training kits seemed to lower expectations of skill requirements to conduct CPR training, but only among those who were familiar with such kits.Conclusions To facilitate implementation of CPR training in schools, it is necessary to have clear guidelines regarding the required proficiency level to train students in CPR, to provide teachers with these skills, and to underscore that extensive skills are not required to provide CPR. Further, it is important to familiarise teachers with CPR training kits.